2016
DOI: 10.1088/1748-6041/11/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

Injectable hydrogels embedded with alginate microspheres for controlled delivery of bone morphogenetic protein-2

Abstract: Some delivery carriers with injectable characteristics were built using the thermosensitive chitosan/dextran-polylactide/glycerophosphate hydrogel and selected alginate microspheres for the controllable release of bone morphogenetic protein-2 (BMP-2). BMP-2 was first loaded into the microspheres with an average size of around 20 μm and the resulting microspheres were then embedded into the gel in order to achieve well-controlled BMP-2 release. The microsphere-embedded gels show their incipient gelation tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…Thus, the hydrogel could maintain the growth factor for a much longer time. Another case involved the encapsulation of the BMP‐2 microspheres into chitosan‐based hydrogels for its sustainable release . The two studies above confirmed the hydrogels, after being loaded with BMP‐2, showed significant abilities to induce the bone regeneration in vivo .…”
Section: Multiple Applicationsmentioning
confidence: 83%
“…Thus, the hydrogel could maintain the growth factor for a much longer time. Another case involved the encapsulation of the BMP‐2 microspheres into chitosan‐based hydrogels for its sustainable release . The two studies above confirmed the hydrogels, after being loaded with BMP‐2, showed significant abilities to induce the bone regeneration in vivo .…”
Section: Multiple Applicationsmentioning
confidence: 83%
“…Therefore, these carriers can be incorporated in the hydrogel to avoid a burst release of bioactive molecules from hydrogel because the hydrogel provide an extra diffusion barrier for drug release which increases the drug release period. There are many research based on the utilization of composite systems (microparticle embedded hydrogels) for control the drug or growth factor release . Delie and coworkers developed an easily applicable drug delivery system for the prevention of intimal hyperplasia, through a single administration of a cross‐linked hyaluronic acid hydrogel/poly‐lactic‐co‐glycolic acid (PLGA) microparticle formulation loaded with atorvastatin.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, type-I collagen content was also quantified using a collagen type I ELISA kit (rabbit) (US Biological, Salem, MA, USA). Alkaline phosphatase (ALP) activity was assessed while using an ALP assay kit (Abcam, Cambridge, MA, USA), and the ALP activity was normalized to the total protein content [45]. These quantitative measurements were performed following the protocols and instructions provided by manufactures.…”
Section: Methodsmentioning
confidence: 99%